(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article analyzes global trends in the development of digital payment technologies and their role in transforming payment systems under modern economic conditions. In particular, it highlights the growing share of cashless transactions, the expansion of mobile payments and electronic wallets, the development of QR payments and contactless technologies, as well as the increasing influence of large technology companies (BigTech) in shaping payment ecosystems. The study examines the impact of digital payments on reducing transaction costs, accelerating financial operations, increasing transparency in economic processes, and reducing the scale of the shadow economy. The findings suggest that the further development of digital payment technologies requires improvement of the institutional and regulatory framework, strengthening of cybersecurity, and enhancement of user trust in digital financial services.